The Effect of Special Exercises For Developing Transitional Speed Of Field Referees In Iraqi Soccer Primer League - Abed al kareem, Mustafa; Qassim, Sabah (Journal of Physical Education, 2019)
The research aimed at amending transitional speed of soccer referees test, designing special exercises for developing speed, and identifying the effect of exercises on transitional speed through the amended test for Iraqi primer league referees. The researchers used the experimental method on (38) referees from the season (2018 – 2019) and selected only (15) from Baghdad. The test was applied then the data was collected and treated using proper statistical operations to come up with the results.